Mycoplasma pneumoniae Infection in Children Is a Risk Factor for Developing Allergic Diseases - Qing Ye; Xiao-Jun Xu; Wen-Xia Shao; Yan-Xiang Pan; Xue-Jun Chen (The Scientific World Journal)
Mycoplasma pneumoniae (MP) infection is the dominant cause of pneumonia in children. We sought to determine the relationship between MP infection and secondary allergic disease and to clarify the associated mechanisms of inflammatory response. A prospective study was performed among 1330 patients diagnosed with pneumonia to investigate the patient immune status by determining the correlation between MP infection, immunoglobulin E (IgE) levels, and a spectrum of associated serum cytokines. Serum IgE, IL-4, IL-6, and IL-10 levels for MPP patients in the acute phase were obviously higher than those in the recovery phase (P<0.01). MPP patients with allergic conditions had increased serum IgE levels and increased IL-4/INF-γ ratio, and IgE and Eosinophil Cationic Protein were further elevated in patients who eventually developed secondary asthma changes. Patients with severe pneumonia and high clinical pulmonary infection scores presented higher levels of IL-4 and IL-5 in serum than those with low scores (P<0.01). The proportion of CD4+ and CD8+ T cells that secreted IL-4 was significantly increased in MPP patients with elevated IgE. Our data demonstrate a significant correlation between MP infection and IgE levels, which is associated with a Th1/Th2 cytokine imbalance.